Gyrodactylus angorae (Monogenea: Gyrodactylidae): First Occurrence on the Body of Two Nemachilid Fishes from Iraq - Younis S. Abdullah (Zanco Journal of Pure and Applied Sciences, 2021)
The monogenean Gyrodactylus angorae Ergens & Ibragimov, 1979 was identified on the skin, fin and gills of two nemacheilid loaches Oxynoemacheilus zarzianus Freyhof & Geiger, 2017 and Eidinemacheilus proudlovei Freyhof, Abdullah, Ararat, Hamad & Geiger, 2016 from Tabin Stream, Sulaimani Prvovince, Kurdistan Region, Iraq for the first time. The description and measurements of this parasite are given in the present study. The prevalence and mean of intensity were also shown.